Hazard Analysis and Occupational Safety and Health Risk (K3) with Hazard Identification Risk Assessment and Determining Control (HIRADC) in the Canopy Making Process at the Arivlas Workshop, Bantul Regency. - Cahyadi, Nur; Arianto, Machfudz Eko (Universitas Ahmad Dahlan, 2024)
Background: Most workers have not complied with the standard operating procedures in the use of personal protective equipment (PPE), apart from the lack of awareness of workers about the importance of using PPE, there are other factors, namely the Arivlas Workshop in Bantul Regency does not have occupational safety and health risk management so that the existing risks cannot be controlled which will cause the risk of work accidents when using machines, equipment and during the installation process. Method: This study is descriptive with a qualitative type of research that aims to obtain an overview of the analysis of safety and health risks in the canopy making process at the Arivlas Workshop in Bantul Regency. The research subjects were taken by purposive sampling, using HIRADC tools with data collection techniques through observation and interviews. The respondents in this study were 3 workers as the main informants, and workshop owners as key informants. Result: In the canopy making activity, a risk assessment of 20 risks included in the moderate risk category was still tolerable but action or handling was needed so that the risk could be reduced, and 15 high risks were unacceptable so attention was needed to take action or handle as soon as possible. Conclusion: The process of making canopies at the Arivlas Workshop in Bantul Regency has a high potential for hazards and risks to occupational safety and health, the dangers contained in canopy making activities are the dangers of movement, gravity, mechanics, electricity, chemicals, noise, and radiation. With the risk of hearing loss, feet hit by iron, scratches, electric shocks and the risk of inhaling chemicals such as paint and dust from polishing results.